A Comparative Study Of Two Different Approaches In Teaching Thermodynamics - Hassan, Onn; Mat, Ramli (2005)
A preliminary study has been carried out to compare the outcome of two different approaches in teaching thermodynamics. The results from the first year undergraduate students taking the subject for the first time in two classes conducted by different lecturers using different approaches indicate that the impact on the top half of the class is not significant whereas to the other half the approaches may have some bearing on the performance of the students.